ON THE PROBLEM OF THE TREATMENT OF GENITAL LICHEN PLANUS - Yu. A. Molochkova (Исследования и практика в медицине)
Lichen planus is a chronic inflammatory disease of the coated flat nonkeratinizing epithelium of the skin and mucous membranes. Still etiology of this disease is not completely clear. At the same time, many researchers have expressed their views in favor of the theory of occurrence of autoimmune planus. The emergence of this disease may also be associated with infectious diseases, trauma, hormonal disorders, and hereditary predisposition. Currently, standard treatment of lichen planus is topical application of corticosteroids. With the lack of effectiveness of the last clinicians suggest topical calcineurin inhibitors. That less, all treatments planus today are ineffective. Researchers continue to search for more effective treatments for this pathology. At this point in the treatment of various diseases is well proven photodynamic therapy. Given the high efficacy of photodynamic therapy in the treatment of basal cell carcinoma, actinic keratosis and various other skin diseases, clinicians began to fully explore the impact of the use of photodynamic therapy in the treatment of lichen planus.